Association between Discoid Lupus erythematosus and Cigarette Smoking - A case-control study - Miot, Hélio Amante [UNESP]; Miot, LDB; Haddad, G. R. (Karger, 2005)
Background. Discoid lupus erythernatosus (DLE) is a chronic cutaneous disease affecting photoexposed areas and has also been associated with cigarette smoking. Objective: To evaluate the association between smoking and DLE. Methods: A case-control study was performed involving 57 cases diagnosed with DLE and 215 healthy controls. Results:A higher smoking prevalence was noted in DLE cases (84.2%) than controls (33.5%), and the odds ratio adjusted for gender, age and ultraviolet index in the city of origin was 14.4 (95% confidence interval 6.2-33.8; multiple logistic regression, p < 0.01). The cumulative smoking exposure was not related to premature DLE development. At the beginning of the disease, smokers had more extensive involvement than nonsmokers; compromise of the upper arms was statistically related to smoking. Conclusion: Cigarette smoking was statistically associated with DLE development. Other studies are needed in order to evaluate the effects of smoking cessation on the course of disease. Copyright (c) 2005 S. Karger AG, Basel.
Keywords: cigarette smoking; Discoid Lupus erythematosus